The Distributions and Boundary of Two Distinct, Local Forms of Japanese Pond Frog, Pelophylax porosus brevipodus, Inferred From Sequences of Mitochondrial DNA - Nagai, Yukari; Doi, Toshio; Ito, Kunio; Yuasa, Yoshiaki; Fujitani, Takeshi; Naito, Jun-ichi; Ogata, Mitsuaki; Miura, Ikuo (Frontiers in Genetics, 2018)
The Nagoya Daruma pond frog Pelophylax porosus brevipodus is distributed in western Japan and is traditionally divided into two local forms: the Okayama form in the west and the Nagoya form in the east. These two forms are genetically differentiated, but have never been defined taxonomically because their distributions are unclear to date. To complete the distributions and identify the boundary of the two forms, we genetically investigated 16 populations including eight populations located within the unexamined area. We found that the distributional boundary is located within a small area of Hyogo Prefecture where haplotypes of mitochondrial cytochrome b (cytb) and D-loop region corresponding to the two forms co-existed. On the other hand, the polymorphic site of the nuclear gene SOX3 revealed introgression over the boundary into Okayama cytb clade. These results suggest that the two forms were geographically isolated from each other in the past, and secondarily contacted and then accepted one-way introgression. As a next step of the research, taxonomic approach is expected to define the two forms.